Gambaran Keterlibatan Ayah Dalam Perkembangan Identitas Diri Anak Usia Dini Di Tk Miftahussa’adah Samarang Kec. Samarang - Elia Wardani; Ai Siti Habsoh (LP2M STAI Al-Musaddadiyah Garut, 2026)
This research is motivated by the minimal involvement of fathers in school activities. In many instances, father participation is rarely seen, such as during child drop-off, art performances, report card distribution, or farewell events. In addition to work-related factors, this situation is also exacerbated by the lack of school programs that specifically engage fathers in activities with their children. This study aims to describe the involvement of fathers in the development of self-identity in early childhood. The research employs a quantitative approach with a correlational method, with a sample consisting of 45 parents of students aged 2-6 years. Data collection techniques use questionnaires, and the data is analyzed with the help of IBM SPSS Statistics version 26. The analysis results obtained a t value of 2.354 with a significance level of 0.05 and a t table of 2.015. The results of the calculation show t calculated > t table (2.354 > 2.015), thus concluding that there is a significant effect of father involvement on the development of self-identity in early childhood. The coefficient of determination (R-Square) value of 0.114 indicates that father involvement contributes 11.4% to the development of children's self-identity, while 88.6% is influenced by other variables outside of this study. Keywords: Father Involvement, Self-Identity, Early Childhood.